Effects of Mild Orthostatic Stimulation on Cerebral Pulsatile Hemodynamics - Ninomiya, Yuka; Tomoto, Tsubasa; Ogoh, Shigehiko; Imai, Tomoko; Takahashi, Koki; Sugawara, Jun (Frontiers in Physiology, 2019)
The augmented cerebral hemodynamic pulsatility could lead to the elevated risk of cerebrovascular disease. To determine the impact of an acute orthostatic challenge on a pulsatile component of cerebral hemodynamics, mild lower body negative pressure (LBNP, -30 mmHg) was applied to 29 men. Middle cerebral artery blood flow velocity (MCAv) was measured by transcranial Doppler technique. Stroke volume (SV) was estimated by the Modelflow method with adjustment by the Doppler ultrasound-measured SV at rest. SV, peak and pulsatile MCAv, and pulsatility index were significantly lower during the LBNP stimulation than those at the baseline (e.g., supine resting) (P<0.05 for all), whereas mean arterial pressure and mean MCAv remained unchanged. The change in SV with the LBNP stimulation significantly correlated with corresponding changes in peak and pulsatile MCAv (r=0.617, P<0.001; r=0.413, P=0.026, respectively). These results suggest that pulsatile components of cerebrovascular hemodynamics are dampened during the transient period of orthostatic challenge (as simulated using LBNP) when compared to supine rest, and which is partly due to the modified SV.